Slovenski Afričani - Palaić, Tina (Etnolog. Nova vrsta (Ljubljana), 2017)
The article presents the results of a research conducted for a section of an exhibition that will be staged by the Slovene Ethnographic Museum as part of the European SWICH project. The African Slovenes who participated in the research came to Slovenia to study here thanks to the social conditions in the former Yugoslavia, and they stayed here after graduating. The authors first analyze the participation of the African Slovenes, reflecting on the democratisation of museum practices and the power relationship that emerged in the process of the participation, based on concepts like epistemic justice, the joint responsibility of heritage researchers and carriers, and radical transparency. The principal focus was on analyzing how the interlocutors identified themselves, as expressed through their choice of personal objects.The article presents the results of a research conducted for a section of an exhibition that will be staged by the Slovene Ethnographic Museum as part of the European SWICH project. The African Slovenes who participated in the research came to Slovenia to study here thanks to the social conditions in the former Yugoslavia, and they stayed here after graduating. The authors first analyze the participation of the African Slovenes, reflecting on the democratisation of museum practices and the power relationship that emerged in the process of the participation, based on concepts like epistemic justice, the joint responsibility of heritage researchers and carriers, and radical transparency. The principal focus was on analyzing how the interlocutors identified themselves, as expressed through their choice of personal objects.
Keywords: materialna kultura; spominski predmeti; identiteta; Afričani; Slovenia; Slovenija; Slovenski etnografski muzej; Ljubljana; muzejske zbirke; razstave